Immunomodulatory drug- and proteasome inhibitor-backbone regimens in the treatment of relapsed multiple myeloma: an evidence-based review. Issue 9 (1st September 2020) - Sanchez, Larysa; Barley, Kevin; Richter, Joshua; Franz, Joseph; Cho, Hearn Jay; Jagannath, Sundar; Madduri, Deepu; Parekh, Samir; Richard, Shambavi; Chari, Ajai
ABSTRACT: Introduction: Recent advances and drug approvals in the last decade have substantially changed the landscape of relapsed and refractory multiple myeloma (RRMM), which not only improved outcomes for patients but also increased complexity of treatment decisions. The approvals are based on randomized studies of novel agents added to an immunomodulatory drug- (IMiD) or proteasome inhibitor (PI)-backbone showing an improvement in outcomes. However, differences in enrolled patient populations/study designs limit comparisons of results, making the choice and sequencing of agents challenging. Areas covered: This review summarizes the latest updates of key clinical trials of IMiD- and PI-backbone regimens in RRMM. Additionally, it highlights carfilzomib dosing strategies and toxicity profiles of varying carfilzomib combination regimens and provides a clinical guideline for the use of carfilzomib therapy. PubMed and relevant meeting (ASH, ASCO, EHA, IMW) databases from 2010 to 2020, as well as clinicaltrials.gov, were queried for this review. Expert opinion: The choice of therapy for RRMM requires careful consideration of patient factors (age/frailty and comorbidities), disease factors (symptom burden/biology), and treatment-related factors (toxicities/responses to prior therapies). Importantly, a critical factor in selecting an agent based on the published data is a patient's sensitivity to lenalidomide and bortezomib at the time of relapse.